A Study of optoelectronic and environmental factors affecting the accuracy of vehicle-mounted licence plate recognition - Rademeyer, Martin Christian (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.